2004
DOI: 10.1002/eji.200324703
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CD4loCD40+ auto‐aggressive T cell expansion during insulin‐dependent diabetes mellitus

Abstract: The generation of auto-aggressive T cells involves failure of central or peripheral tolerance. We previously demonstrated that peripheral CD4 lo CD40 + T cells give rise to pathogenic T cells in the non-obese diabetic (NOD) model. Here we show that peripheral CD4 + CD40 + T cells from diabetic or pre-diabetic NOD mice induce insulin-dependent diabetes mellitus. Consistent with breach of peripheral tolerance, CD4 lo CD40 + T cells expand with age in NOD mice but not in MHC-matched non-obese resistant (NOR) or B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
134
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(146 citation statements)
references
References 35 publications
(73 reference statements)
10
134
0
2
Order By: Relevance
“…1 and Table I). Although the increase in CD40 ϩ cells in CIA vs control mice is modest compared with genetically predisposed autoimmune-prone strains of mice (14,17), it is consistent with the FACS profile of T cells from normal mice (9,17,67). Strains of mice that are prone to spontaneous autoimmune disease have robust expression of CD40 by T cells, whereas nondisease prone strains do not (14), so it is not surprising that C57BL/6 mice do not have as robust proportions of CD40 ϩ T cells as strains that develop autoimmune diseases relatively early in life.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…1 and Table I). Although the increase in CD40 ϩ cells in CIA vs control mice is modest compared with genetically predisposed autoimmune-prone strains of mice (14,17), it is consistent with the FACS profile of T cells from normal mice (9,17,67). Strains of mice that are prone to spontaneous autoimmune disease have robust expression of CD40 by T cells, whereas nondisease prone strains do not (14), so it is not surprising that C57BL/6 mice do not have as robust proportions of CD40 ϩ T cells as strains that develop autoimmune diseases relatively early in life.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of CD40-expressing T cells or autoantibodies is not enough to develop autoimmunity. NOR mice, like their NOD counterparts, have CD40-expressing T cells, yet do not develop disease (17). Similarly, the presence of autoantibodies does not necessarily indicate pathogenesis (77)(78)(79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In numerous studies CD40 has been identified as a biomarker for auto-aggressive T cells (19,28,(32)(33)(34)(35)(36). A panel of highly pathogenic, auto-aggressive T cell clones, including the well described BDC2.5 clone express CD40 (34)(35)(36).…”
Section: Th40 Cells: a Biomarker For Pathogenic Effector T Cellsmentioning
confidence: 99%
“…A panel of highly pathogenic, auto-aggressive T cell clones, including the well described BDC2.5 clone express CD40 (34)(35)(36). Although CD40 has been typically associated with antigen presenting cells, it was demonstrated on primary T cells in NOD mice, the type 1 diabetes model, and in the process identified a unique effector CD4 + T cell population, characterized as CD4 + CD40 + [Th40] (19,28,(32)(33)(34)(35)(36)(37). Importantly, Th40 cells were detected in both autoimmune and non-autoimmune mouse strains but occurring at a significantly greater percentage and cell number in autoimmunity (19,28,(32)(33)(34)(35).…”
Section: Th40 Cells: a Biomarker For Pathogenic Effector T Cellsmentioning
confidence: 99%